2007
DOI: 10.21608/asat.2007.24386
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Compressor Blades Under Extension, Bending and Torsion Loads

Abstract: A finite element formulation is presented for modeling the dynamic as well as static response of a compressor blades subjected to extension, bending and torsional loads. The formulation is derived from the variational principle with the consideration for the total potential energy of the structure based on the classical lamination theory. The compressor blade is modeled as an advanced beam with idealized rectangular cross-section that takes the warping effect into consideration. The bending-torsion coupling is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…, where,  is the fundamental natural frequency. Tables (7) and (8) show a good agreement between the predicted results of the fundamental natural frequencies of the proposed model with the results given by Ref. [3] Figures (10)a, (10)b and (10)c represent the effect of ply-orientation angles on the first three mode shapes of a composite beam with clampedfree boundary condition.…”
Section: B) Dynamic Analysissupporting
confidence: 74%
See 1 more Smart Citation
“…, where,  is the fundamental natural frequency. Tables (7) and (8) show a good agreement between the predicted results of the fundamental natural frequencies of the proposed model with the results given by Ref. [3] Figures (10)a, (10)b and (10)c represent the effect of ply-orientation angles on the first three mode shapes of a composite beam with clampedfree boundary condition.…”
Section: B) Dynamic Analysissupporting
confidence: 74%
“…Elshafei et al [8,9] proposed a finite element model, to study the static and the free vibration response of isotropic and anisotropic beams subjected to axial, bending, and torsion loads with warping effect using the classical beam theory. They found that an additional node in the middle of the beam element was required to give a better presenting in the torsion deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The displacements field equations of the beam are assumed as [5]: Selecting the constant values of Eqn. (1)a as:…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…Elshafei, et al [5,6] proposed a finite element model to study the static and the free vibration response of isotropic and anisotropic beams subjected to axial, bending, and torsion loads with warping effect using the classical beam theory. They found that an additional node in the middle of the beam element is required to give a better twisting Proceeding of the 14 th AMME Conference, 25 -27 May 2010…”
Section: Introductionmentioning
confidence: 99%
“…The torsion deformation of the beam cross section subjected to a torque moment is shown in Fig. 3 and Fig 4, and the following formulations are obtained [19].…”
Section: Theoritical Formulationmentioning
confidence: 99%